2018
DOI: 10.1002/chem.201802748
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Bambusurils for Enantioselective Recognition of Carboxylate Anion Guests

Abstract: Synthesis of the first enantiomerically pure chiral bambusurils is reported. The bambusurils were prepared on the gram scale without using any chromatography techniques. The bambusurils formed supramolecular complexes with all tested chiral carboxylates including amino acids and drug molecules with the enantioselectivity ranging from 1.1 to 3.2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 32 publications
0
28
0
1
Order By: Relevance
“…Following the protons that point inside and outside of the cavity of macrocycle (see SI, Figure S18), confirms that external complexes with fast exchange on the NMR time scale are formed. Previously, 1:1 and 1:2 binding of carboxylic acids and carboxylates have also been studied for other single-bridged cucurbiturils, the bambus[6]urils 40,54,55 .…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…Following the protons that point inside and outside of the cavity of macrocycle (see SI, Figure S18), confirms that external complexes with fast exchange on the NMR time scale are formed. Previously, 1:1 and 1:2 binding of carboxylic acids and carboxylates have also been studied for other single-bridged cucurbiturils, the bambus[6]urils 40,54,55 .…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…The bambusuril molecules used in this study ( BU C , Figure 1 b) have been synthetized recently [12a] . The chirality of BU C was obtained by introducing chiral glycoluril building blocks together with the attachment of ( S )‐1‐phenylethylamine substituents on the macrocycle, which gave rise to a good enantioselectivity for chiral carboxylates.…”
Section: Resultsmentioning
confidence: 99%
“…The europium nitrate salt was prepared from the corresponding oxide (Aldrich, 99.99 %) and dried according to published procedures. The anion‐free chiral BU C was prepared according to previously described procedures [12a] . Its CD spectrum was recorded with a JASCO 810 spectropolarimeter at 293 K by using a quartz cuvette of 0.1 cm pathway and is given in Figure S10 (in the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantitative conversion to cycHC[6] was reproducibly obtained by aging of products from either 30 or 60 minutes LAG (Table 1 lines 4 and 5, also Table S4). In contrast, milling for only 5 minutes produced waxy, transparent solids ( Figure S4) which, upon aging, gave low and inconsistent conversions to cycHC[6] (Table S4, lines [14][15]. The mechanochemical step was also explored by manual kneading with aqueous HCl, which revealed that the waxy material results from solidification of an initially formed liquid phase.…”
mentioning
confidence: 99%